Alterations in plasma lecithin:cholesterol acyltransferase and myeloperoxidase in acute myocardial infarction: Implications for cardiac outcome - Dullaart, Robin P.F.; Tietge, Uwe J.F.; Kwakernaak, Arjan J.; Dikkeschei, Bert D.; Perton, Frank; Tio, René A. (Atherosclerosis, 2014)
The cholesterol esterifying enzyme, lecithin:cholesterol acyltransferase (LCAT), plays a key role in HDL maturation and remodeling. Myeloperoxidase (MPO) may compromise LCAT enzymatic activity. We tested the extent to which plasma LCAT activity is altered in acute myocardial infarction (MI) in conjunction with abnormal MPO levels. We also assessed the impact of LCAT and MPO on newly developed major adverse cardiovascular events (MACE). Two-hundred one consecutive patients referred for acute chest pain of whom 134 had MI (95 with ST-elevation) participated. Forty-five new MACE were ascertained during 1203 (range 13–1745) days of follow-up among 185 patients. Plasma LCAT activity was measured using an exogenous substrate assay. MPO mass was assayed by chemiluminescent microparticle immunoassay. Plasma LCAT activity was decreased by 15%, coinciding with 7-fold increased MPO levels in acute MI patients vs. patients with non-cardiac chest pain (p < 0.001 for both; correlation: r = −0.343, p < 0.001). MI at admission was associated independently with both lower plasma LCAT activity and higher MPO (age- and sex-adjusted odds ratio per 1 SD increment: 0.46 (95% CI, 0.31–0.68), p < 0.001 and 7.58 (95% CI, 3.34–17.11), p < 0.001, respectively). In an analysis with LCAT and MPO together these associations were modestly attenuated. MPO mass (hazard ratio: 1.59 (95% CI, 1.15–2.19), p = 0.004), but not LCAT activity (hazard ratio: 0.87 (95% CI, 0.65–1.19), p = 0.39), predicted newly manifest MACE. In acute MI patients, plasma LCAT activity is decreased coinciding with increased MPO levels. Higher MPO but not lower LCAT activity prospectively predicts adverse cardiac outcome. •Lecithin:cholesterol acyltransferase (LCAT) activity is instrumental in HDL remodeling.•Myeloperoxidase (MPO) may compromise LCAT activity.•LCAT activity was decreased, coinciding increased MPO levels in acute MI patients.•Higher MPO but not lower LCAT activity prospectively predicted adverse cardiac outcome.